An evaluation of the Business Model Canvas by technology-oriented startups in Brazil : a qualitative study about the usage of the tool by Brazilian entrepreneurs - Schwarzkopf, Jan (2016)
The following paper was conducted with the support of several entrepreneurs and startups from Brazil. The aim of the research was to find out which impact the Business Model Canvas, further abbreviated as BMC, has on technology-oriented startups in Brazil. The first step of the study was identify some general concepts of entrepreneurship, as well as the conditions and environment of the country. Afterwards, it was focused on defining and comparing different business model tools and concepts to the BMC. After the literature review and meeting with several professionals in the area of entrepreneurship and startups, a questionnaire was formulated in order to conduct the qualitative study and identify the main impact of the tool. The questionnaire was answered by ten startups. In order to check the validity and credibility of the research outcomes, theory and investigator triangulation was used. As a result, the usage of the BMC could be evaluated by obtaining the outcomes and the theory, which showed that Brazilian tech startups are using Osterwalder’s model for the reason of idea creation and testing, validating and pivoting their business model. Interestingly, the research revealed that the entrepreneurs are using the tool often not in the traditional way of printing it, but rather applying it as a thinking approach. Besides, the entrepreneurs are focusing mostly on developing a strong Value Proposition, Customer Segment and sustainable Revenue Streams, while afterwards the remaining building blocks are built. Moreover, the research showed that the startups are using also other concepts, such as the Customer Development Process or Build-Measure-Learn Feedback Loop. These methodologies are often applied together with the BMC and helps to identify the most sustainable components of the business idea. Keywords: Business